1980
DOI: 10.1063/1.439688
|View full text |Cite
|
Sign up to set email alerts
|

Electronic energy transport in substitutionally disordered molecular crystals

Abstract: In this paper we present a theoretical study of incoherent electronic energy transfer (EET) in an impurity band of substitutionally disordered, mixed, molecular crystals. Dispersive diffusion of the electronic excitation was treated by an Average Dyson Equation Approximation (ADEA) to the master equation for EET. The ADEA rests on expressing the Green’s function (GF) for the probability of site-excitations in a single fixed spatial configuration in terms of a Dyson equation with a normalized vertex function an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…• The energy-independent version of this approximation has seen considerable use in non-self-consistent theories of energy transport. 17…”
Section: Ei)gs(e I )mentioning
confidence: 99%
“…• The energy-independent version of this approximation has seen considerable use in non-self-consistent theories of energy transport. 17…”
Section: Ei)gs(e I )mentioning
confidence: 99%
“…The basic physics of EET is well-studied, especially in the limit of the incoherent dipole-dipole interaction, or Forster resonance energy transfer (FRET). In this limit, Forster and later investigators [8][9][10][11][12][13] have shown how FRET occurring between identical chromophores in a concentrated sample leads to an effective diffusion constant for the excitation,…”
Section: Introductionmentioning
confidence: 99%
“…Various factors may complicate the application of such models to real polymeric systems. Such complications include the small distances between chromophores (on the order of a few Angstroms, small compared to molecular dimensions of tens of Angstroms) which preclude the use of the point dipole model, 6 the amount of local disorder (both energetic and orientational), [7][8][9][10] and the possibility that energy transfer occurs on a time scale faster than intramolecular vibrational relaxation (hot transfer). 11 All these factors may be taken into account to at least some degree by modifications of the standard Förster model.…”
Section: Introductionmentioning
confidence: 99%